POLITICAL STABILITY IN THE DIMENSION OF THE CHALLENGES OF THE INFORMATION AGE - Komarova, Tetiana (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2024)
The issues of stability / instability of modern society and the state, factors of overcoming destructive phenomena are considered. Among the most important factors, the excessive growth of uncertainty, polyvariance, randomness in modern political development are highlighted. The substantive core of the crisis of political stability is explained and the reasons for the increase in the price of social and political conflicts under conditions of social tension are revealed. The factors and conditions for the emergence and development of political conflicts are determined. The greatest danger of value-based conflicts and the clash of identities is emphasized. The formation of a new - global - identity is indicated as the basis for a kind of elite circle of the information age. The essence and features of the phenomenon of post-under-information are studied as a continuation of the theoretical logic of the concept of post-under-modernity. The presence of certain characteristic features of identity, inherent in the industrial era, which were manifested in value preferences and motivations, is noted. Special attention is paid to revealing the issue of the features of the explication of the concept of political stability at the present stage. The processes of formation of identities and their corresponding value meanings under the conditions of globalization and informatization, which affect all spheres of social life, determine the emergence of contradictions and conflicts, are analyzed. The multi-component nature of the selection of identities that coexist, collide, and affect the growth of dysfunction in the political sphere both at the local and global levels is analyzed. This leads to the growth of destructive phenomena. The principles of the formation of social hierarchies and elites, the features of the «digital divide» at the interindividual, social and inter-social levels are studied. It is determined that technological development can be combined with stagnation, or even regressive manifestations in other areas of social and political life. Examples of this are glamorization, carnivalization of political processes, the growth of the trend of scandal politics as a political phenomenon, populism, and the statistical advantage of authoritarian practices in the world, which, unfortunately, correlates with the corresponding trend in the information space, in the plane of global transmission of value meanings. Thus, technologies are «digested» by social practices in accordance with their needs and goals. Certain value meanings are analyzed, which within the framework of identity formation contribute to social adaptation and political stabilization. The logic of the exacerbation of contradictions in the dimension of such priority axiological meanings as freedom, democracy, stability is proved